The prevalence of cancer in Britain before industrialization. Issue 17 (4th May 2021) - Mitchell, Piers D.; Dittmar, Jenna M.; Mulder, Bram; Inskip, Sarah; Littlewood, Alastair; Cessford, Craig; Robb, John E.
Abstract : Background: To plan for cancer services in the future, the long view of cancer prevalence is essential. It might be suspected that cancer prevalence before tobacco and industrial revolution pollutants was quite different to today. Methods: To quantify the degree to which cancer prevalence may be changing over time, the authors analyzed 143 skeletons from 6 cemeteries from the Cambridge area (6th‐16th centuries). Visual inspection coupled with screening using both plain radiographs and computed tomography scans was used to detect malignant lesions. Results: A total of 3.5% of individuals showed evidence for metastases. Factoring in modern data for the proportion of those with cancer that die with bone metastases, this suggests a minimum prevalence of all cancers at the time of death in medieval Britain to be approximately 9% to 14% of adults. Conclusions: This figure compares with a 40% to 50% prevalence of cancer at the time of death for modern Britain. The difference may be explained by the effects of modern carcinogens, the spread of viruses that trigger malignancy, industrial pollutants, and longer life expectancy. Lay Summary: Until now, no one has been able to work out how common cancer was before the time people were exposed to tumor‐inducing chemicals from tobacco and industrial factories. In this novel study, the authors have determined the percentage of people living in medieval Britain who had cancer metastases to bone at the time of their death and then compared that with modern data. It was found that cancer was approximately 25% as common in medieval times as it is today. This article suggests cancer was much more widespread in medieval times than was previously realized. Abstract : The authors have found that in medieval Britain, cancer was likely present in 9% to 14% of adults by the time of their death. This is considerably lower than the 40% to 50% figure for the modern populations and highlights the increase in cancer prevalence.